Local development from a sociocultural perspective of competitiveness - Echeverry Romero, Ruben Dario; Medina Vasquez, Javier Enrique; Silva Castellanos, Tulio Ferney (Cuadernos de Administración, 2013)
This article summarizes a sociocultural perspective of competitiveness as a result of applied work performed by the Research Group in International Business and Foreign Trade, in partnership with the Foresight, Innovation, and Knowledge Management Institute at Universidad del Valle, in consultation exercises for municipal governments, specifically in Palmira and Buenaventura (Colombia). This perspective becomes practical in a methodology that begins with the creation of a regional competitive profile, continues with the definition of thematic groups identified to facilitate further delving into and treatment of regional competitiveness problems and defines an optimal setting for consensus building strategies. In its application, it has been possible to verify that the theme and types of problems identified were generically common in both municipalities. Despite the heterogeneous nature of the experiences, it was possible to formulate a set of indispensable strategies in the Local Development Agendas for similar municipalities in developing countries. This article is a fundamental contribution to the whole experience of building regional development processes based on recognizing the particular characteristics of the location.